Friabilimeter Calibration - White, F. H. (BrewingScience, 1998)
BackgroundIn 1997, investigations into reported differences in friability revealed that calibration standards amongst friabilimeter users in some areas of Europe appeared to have drifted by varying degrees. The situation was further complicated when it was learnt that, without any announcement of a change, the manufacturer of the friabilimeter, Pfeuffer GmbH, had been asked to make an upward adjusment of 2.5% friability to the calibration of the working standards friabilimeter.